The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1007/s00018-003-2169-x
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin: a pregnancy hormone as central player of body fluid and circulation homeostasis

Abstract: The peptide relaxin has long been regarded as an important hormone of pregnancy, contributing to changes in connective tissue composition as well as to regulation of implantation, myometrial activity and labor. On the other hand, the astonishing pleiotropy of this hormone escaped scientific awareness. This review focuses on new facets of relaxin, including its antifibrotic effects, its role in the control of pituitary hormone release, its vasodilator and pro-angiogenic properties and its versatile myocardial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 174 publications
0
4
0
Order By: Relevance
“…46 Interestingly, increased production of relaxin, a hormone secreted by the corpus luteum to relax the pelvic ligaments and a potent vasodilator, may contribute to the increased venous pressures in the lower extremities. 47,48 A recent study published in Circulation used a machine learning approach and confirmed many of the known risk factors but also identified several new strong predictors, including leg bioimpedance and height. 6 Height had been identified as a potential risk factor in an early epidemiological study several decades ago 50 but had been inconsistently reported since.…”
Section: Venous Disease Epidemiologymentioning
confidence: 97%
“…46 Interestingly, increased production of relaxin, a hormone secreted by the corpus luteum to relax the pelvic ligaments and a potent vasodilator, may contribute to the increased venous pressures in the lower extremities. 47,48 A recent study published in Circulation used a machine learning approach and confirmed many of the known risk factors but also identified several new strong predictors, including leg bioimpedance and height. 6 Height had been identified as a potential risk factor in an early epidemiological study several decades ago 50 but had been inconsistently reported since.…”
Section: Venous Disease Epidemiologymentioning
confidence: 97%
“…Serelaxin (RLX; synonyms: recombinant human relaxin, rhRLX) designates the pharmaceutical form of the human natural hormone relaxin-2 (RLX-2; H2 RLX) suitable for clinical use. In recent years, robust evidence has been accumulating that RLX can markedly reduce tissue and cell damage induced by ischemia and reperfusion (IR) [ 1 , 2 , 3 ]. Such a protective effect has been consistently observed in diverse experimental models, spanning from organ IR in whole animals (heart, gut, kidney) [ 4 , 5 , 6 , 7 , 8 ] and in isolated and perfused organs (heart, lung, liver) [ 9 , 10 , 11 , 12 ] to specific cell types (cardiomyocytes, trophoblast) subjected to in vitro hypoxia (associated or not with nutrient starvation) and reoxygenation [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…RLN1 and 2 were reported to increase the collagen solubility in the cervix of the uterine, as well as to soften the pubic symphysis in the pregnant women (Hansell et al, 1991; Sherwood, 2004; Schwabe and Bullesbach, 2007). The RLN peptide family consists of seven members and produced by interstitial cells of various organs (Dschietzig and Stangl, 2003; Park et al, 2005; Kong et al, 2010). Further studies reported that cardiac cells are able to produce and secrete RLN and their receptors were identified in the heart (Taylor and Clark, 1994; Hsu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%